Design and Implementation of E-Government Applications to Improve Public Service Efficiency in Margahayu District - Rafli Ferdiansyah; Novi Rukhviyanti (CV. Publikasi Indonesia, 2024)
Improving the efficiency of public services in Margahayu District is crucial in facing the development of information and communication technology. In this context, the implementation of E-Government applications is an attractive option because it has the potential to overcome traditional administrative constraints and increase transparency and public participation in public decision making. The implementation of the E-Government application in Margahayu District is expected to provide benefits in improving the efficiency of public services, this writing aims to improve public services to the community, simplify the administrative process, and manage public service data at the sub-district level. The focus of the study uses methodological measures including literature study to understand the concept of E-Government, relevant technologies, and successful implementation in similar contexts, data collection through interviews with related parties in Margahayu sub-district and analysis of existing public service data. Application design using the Waterfall software development model. The results showed that the E-Government Application can improve the efficiency of public services in Margahayu District such as creating, managing population letters, being able to see the results of reports on what types of residence letters have been made, and facilitating service officers in the process of administering and managing public service data in Margahayu District.